2022
DOI: 10.1038/s41467-021-27936-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-expressed BTNL2 facilitates tumour immune escape via engagement with IL-17A-producing γδ T cells

Abstract: Therapeutic blockade of the immune checkpoint proteins programmed cell death protein 1 (PD-1) and cytotoxic T lymphocyte antigen 4 (CTLA4) has transformed cancer treatment. However, the overall response rate to these treatments is low, suggesting that immune checkpoint activation is not the only mechanism leading to dysfunctional anti-tumour immunity. Here we show that butyrophilin-like protein 2 (BTNL2) is a potent suppressor of the anti-tumour immune response. Antibody-mediated blockade of BTNL2 attenuates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…Additionally, our studies did not define the mechanisms by which the tumor microenvironment mediates the accumulation of microbiota-dependent Vγ6 + and microbiota-independent Vγ4 + subsets that aid tumor growth; it is possible that analogous mechanisms to the Btnl-dependent Vγ7 selection are used ( 26 , 27 , 43 , 44 ). In fact, a recent study has suggested that the expression of Btnl2 by tumor cells can specifically recruit protumorigenic IL-17–producing γδ T cells ( 45 ). Although the reduced number of patients and cells analyzed limit broader generalizations regarding public clones, TCR usage biases, and linked signatures, our analyses of infiltrating γδ T cells in human CRC provide an important parallel for the mechanistic details uncovered in murine studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our studies did not define the mechanisms by which the tumor microenvironment mediates the accumulation of microbiota-dependent Vγ6 + and microbiota-independent Vγ4 + subsets that aid tumor growth; it is possible that analogous mechanisms to the Btnl-dependent Vγ7 selection are used ( 26 , 27 , 43 , 44 ). In fact, a recent study has suggested that the expression of Btnl2 by tumor cells can specifically recruit protumorigenic IL-17–producing γδ T cells ( 45 ). Although the reduced number of patients and cells analyzed limit broader generalizations regarding public clones, TCR usage biases, and linked signatures, our analyses of infiltrating γδ T cells in human CRC provide an important parallel for the mechanistic details uncovered in murine studies.…”
Section: Discussionmentioning
confidence: 99%
“…ADORA2A is an adenosine receptor, and blocking tumor-produced adenosine perhaps enhances the effect of immunotherapy ( Raskovalova et al, 2007 ). BTNL2 is considered an effective inhibitor of the antitumor immune response, which has been confirmed in mouse models ( du et al, 2022 ). The high mRNA level of CD160 in CRC has been confirmed in several studies ( Saleh et al, 2020 ; Ma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Patients in the low-risk category of pancreatic cancer may have comparable resistance mechanisms to those seen in breast cancer, where ICOSLG has been shown to be a possible biomarker for the development of trastuzumab resistance [ 72 ]. New clinical evidence shows that BTNL2 expression is elevated following anti-PD-1 treatment, lending credence to the concept that it may play a crucial role in a novel mechanism of cancer immune escape [ 73 ]. An increase in CTLA4 and PD-1 expression was seen in the low-risk group, and anti-PD-1/PD-L1 antibodies were less effective against pancreatic cancer than they were against melanoma, renal cell carcinoma, and non-small cell lung cancer, owing to immunostasis or drug resistance [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%